Let there be two recursive series S and R as follows:(adsbygoogle = window.adsbygoogle || []).push({});

[tex]S_{0} = 0 \quad S_{1} = s \quad S_{n} = 6S_{n-1} - S_{n-2} + p [/tex]

[tex]R_{0} = 0 \quad R_{1} = t \quad R_{n} = 6R_{n-1} - R_{n-2} + p [/tex]

Prove [tex]S_{n}*(R_{n+1} + t - p) = R_{n}*(S_{n+1} + s - p)[/tex]

**Physics Forums - The Fusion of Science and Community**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Recursive Series Equality

Loading...

Similar Threads for Recursive Series Equality | Date |
---|---|

Converting an explicit series to a recursive form | Aug 12, 2014 |

All Square Numbers Follow a Recursive Series? | Jun 19, 2011 |

Recursive series S(n): 8*N*S(n) +1 = square | Nov 18, 2010 |

Recursive series for sum of 2 powers | Jan 21, 2010 |

New recursive series identity | Oct 17, 2007 |

**Physics Forums - The Fusion of Science and Community**